Analisis validasi bahan ajar fisika bermuatan literasi saintifik pada materi alat-alat optik dan pemanasan global - Laras Setia Ningsih; Renol Afrizon; Hidayati Hidayati (Universitas Negeri Padang, 2019)
The 21st century education is expected to create quality human resources and be able to compete in the face of 21st century forecasts. In physics subjects, logical thinking and systematic skills can be developed to equip students to face challenges in an increasingly competitive society. Governments have made various efforts to improve the quality of education. One of them is to apply literacy in learning. However, real conditions at school show that physical learning has not run optimally where literacy is used in learning only functional literation. One solution that can be used to solve this problem is to develop teaching materials with scientific literation. The purpose of this study is to determine the validity of the materials of scientific literacy-charged physics. This type of research is research and development (R & D). The research object is a physics-teaching material charged with the cyanotic literacy of optical tools and global warming for grade XI senior high school. The instrument to validate the teaching material is a questionnaire sheet. It consists of 3 validators, a physics lecturer. Data analysis techniques are descriptive statistics. Based on data analysis, it can be concluded that the average validation value of a physics-led scientific literacy material on the optical tools and global warming is 90.91. Accordingly, physics teaching materials are filled with literacy in materials of optical devices and global warming depending on the very high level of validity.